Impact of oral conditions on the quality of life of elderly caregivers and oral health practices - Barbosa, Liliane Cristina; Moimaz, Suzely Adas Saliba; Saliba, Nemre Adas; Saliba, Tânia Adas (ABCS Health Sciences, 2020)
Introduction: Identifying factors related to the quality of life constitutes strategy for the actions supporting and monitoring the population health. Objective: To assess oral health practices in the elderly, the clinical conditions of oral health of the caregiver and the elderly and oral health-related quality of life of caregiver. Methods: Oral health was evaluated in 388 participants (194 caregivers and 194 elderly) by: the decayed, missing and filled teeth (DMFT) index, the use and need of prosthesis, the Oral Health Impact Profile (OHIP-14) scale and a semi-structured questionnaire. Results: Most caregivers (91.3%) acquired oral health knowledge in daily practice, 33% performed oral hygiene in the elderly and 28% reported difficulties with this activity. The average DMFT was 19.24 for caregivers and 28.70 for the elderly, both with predominance of missing teeth. Prostheses were used by 57.73% of caregivers and 63.40% of elderly. The need of protheses was high, mostly in the mandible, respectively 34.54% and 51.55%. The association between OHIP-14 and the need for total prosthesis showed an impact on the dimensions physical and psychological disabilities. The importance of religion affected the dimension psychological discomfort and physical and psychological disabilities. Caregivers over 60 years old had a 1.2 greater chance of oral health impact on quality of life compared to the 20 to 60-year-old group. Conclusion: The presence of low-value cultural contexts of self-care associated with a positive perception of oral health, even in precarious clinical conditions, minimized the impact on caregivers’ quality of life.